Sistem Pendukung Keputusan Berbasis Web untuk Pemilihan Lokasi Strategis Coffee Shop di Kota Yogyakarta dengan SMART - Siswirawan, Andhika Prasetyo; Fansyuri, Maulana (Teknik Informatika Universitas Pamulang, 2025)
The coffee shop industry in Yogyakarta has grown rapidly along with the increasing coffee consumption and the city’s strong tourism appeal. Selecting a strategic location is a key success factor for coffee shop businesses; however, this process is complex as it involves multiple criteria such as population density, crowd level, accessibility, rental price, and competition. This study aims to develop a web-based Decision Support System (DSS) using the Simple Multi-Attribute Rating Technique (SMART) method to assist entrepreneurs in determining the optimal coffee shop location. The research applied a quantitative approach through several stages: literature review, criteria identification, data collection, system design with UML, implementation using PHP-MySQL, and testing through Black Box and White Box. The results show that the developed system can provide objective, measurable, and user-friendly location recommendations. System testing confirmed that all functions work as designed, while user feedback indicated a high level of satisfaction. In conclusion, the web-based DSS application using the SMART method is effective for selecting strategic coffee shop locations in Yogyakarta. This system provides a practical solution for entrepreneurs to enhance decision-making quality, reduce subjectivity, and support business success in an increasingly competitive market.